THE IMPACT OF EXCESS CARGO LOADED ON THE SERVICE LIFE OF THE PAVEMENT PLAN ON JALAN KHATULISTIWA, SIANTAN HILIR, SUB-DISTRICT PONTIANAK UTARA, KOTA PONTIANAK - Rizki, Devi Novalia; Mukti, Elsa Tri; Kadarini, S. Nurlaily; Said, Said; Sumiyattinah, Sumiyattinah (Fakultas Teknik Universitas Tanjungpura, 2022)
This study aims to review the impact of overload vehicle overload, vehicle damage capacity (VDF) on flexible pavement and decrease the service life of flexible pavement on Jalan Khatulistiwa. The method used is to analyze the service life of pavement based on the cumulative ESAL results for each change in load weight. The survey was conducted on Jalan Khatulistiwa in 2022. The data on vehicle weighing results was obtained from UPPKB Siantan using data in 2021. LHR data was obtained from the Pontianak P2JN office in 2020 and 2021. The study was carried out using the 1993 AASHTO method and the 2017 Highways. From the calculation results in the 20th year, the W18 value for the plan is 96,974,719.09 ESAL and the W18 overload in the 20th year is 110,929,554.2 ESAL. The increase in the value of W18 resulted in a decrease in the service life in the 19th year, namely the Ri value of -1.341% and in the 20th year the value of Ri was -14.390% whereas under normal conditions the value of Ri in the 20th year was 0%. Meanwhile, the remaining life of the plan caused by the addition of a 5% simulation load is the remaining 18,556 years and 100% of the remaining plan life is 9,297 years.